Une question de respect et de sécurité : l’incidence des situations d’urgence sur les langues officielles - Commissariat aux langues officielles (Gouvernement du Canada, 2020)
Nombre de pages: 32

Expérience de francophones en Ontario chez leur médecin de famille : concordance et discordance linguistique - Jutras, Chloé; Gauthier, Alain P.; Timony, Patrick E.; Côté, Daniel; Kpazaï, Georges (La Revue de la Diversité de la Recherche en Santé, 2020)
Abstract : Improving health and health care can be achieved efficiently by improving the patient experience. This study’s main objective was to capture and understand the Francophone patient experience during a visit to their family physician’s office and examining the impact of linguistic concordance or discordance on this experience. Data collection method was inspired by the first two steps of the Experience Based Design approach (EBD), six focus groups were conducted in strong French communities of Northern Ontario in which a total of twenty-nine Francophones described their experience of a visit to their family physicians’ office. The Francophone patient experience is characterized by many emotions, several of which result from the presence of linguistic concordance or discordance with the physician. Linguistic discordance in a primary care setting elicits a less favorable patient experience in terms of emotions associated with comfort, accessibility, security and personal aptitude. Actively offering French language services, being mindful of patient language preferences regardless of apparent bilingualism and providing a bilingual environment in the family physician’s office (e.g. signage, forms) would favor a positive patient experience for Francophones in Ontario.

Perceptions des communautés de langue officielle en situation minoritaire : accès aux services de santé dans la langue officielle de son choix. Rapport final présenté à Santé Canada - Léger (2020)
Ce rapport de recherche sur l’opinion publique présente les résultats d’un sondage Web et de groupes de discussion en ligne menés par Léger Marketing inc. pour le compte de Santé Canada. La recherche a été menée auprès de Canadiens vivant dans une situation où leur langue officielle est minoritaire. Santé Canada, par l’entremise du BACLO, appuie la mise en œuvre d’activités visant à favoriser le dynamisme et le développement des CLOSM ainsi que la pleine reconnaissance et l’usage du français et de l’anglais dans la société canadienne. L’un des principaux objectifs du BACLO est d’améliorer l’accès aux services de soins de santé pour les CLOSM dans la langue officielle de leur choix. Pour documenter cette question, Santé Canada a entrepris un projet de collecte de données quantitatives et qualitatives afin de mieux comprendre les obstacles auxquels les CLOSM peuvent être confrontés pour accéder aux services de santé dans la langue officielle de leur choix, ainsi que les facteurs qui facilitent cet accès. Les résultats de cette étude témoigneront de l’expérience vécue par les CLOSM en matière d’accès aux services de soins de santé dans la langue officielle de leur choix et aideront à identifier les principales lacunes ainsi que les éléments facilitants
Nombre de pages: 169 fs-ref-orig: Léger. (2020). Perceptions des communautés de langue officielle en situation minoritaire : accès aux services de santé dans la langue officielle de son choix. Rapport final. Santé Canada. fs-code-orig: Léger-2020

Perceptions des communautés de langue officielle en situation minoritaire: accès aux services de santé dans la langue officielle de son choix - Sommaire exécutif présenté à Santé Canada - Leger (2020)
Ce rapport de recherche sur l’opinion publique présente les résultats d’un sondage Web et de groupes de discussion en ligne menés par Léger Marketing inc. pour le compte de Santé Canada. La recherche a été menée auprès de Canadiens vivant dans une situation où leur langue officielle est minoritaire. Santé Canada, par l’entremise du BACLO, appuie la mise en œuvre d’activités visant à favoriser le dynamisme et le développement des CLOSM ainsi que la pleine reconnaissance et l’usage du français et de l’anglais dans la société canadienne. L’un des principaux objectifs du BACLO est d’améliorer l’accès aux services de soins de santé pour les CLOSM dans la langue officielle de leur choix. Pour documenter cette question, Santé Canada a entrepris un projet de collecte de données quantitatives et qualitatives afin de mieux comprendre les obstacles auxquels les CLOSM peuvent être confrontés pour accéder aux services de santé dans la langue officielle de leur choix, ainsi que les facteurs qui facilitent cet accès. Les résultats de cette étude témoigneront de l’expérience vécue par les CLOSM en matière d’accès aux services de soins de santé dans la langue officielle de leur choix et aideront à identifier les principales lacunes ainsi que les éléments facilitants
Nombre de pages: 16

Perceptions from official language minority communities : Access to health services in the official language of choice 2020. Executive summary submitted to Health Canada. - Léger (2020)
This public opinion research report presents the results of a web survey and online focus group discussions conducted by Leger Marketing Inc. on behalf of Health Canada. The research was conducted with Canadians living in an official language minority situation. Health Canada, through the OLCDB, supports the implementation of activities to enhance the vitality and developments of OLMCs as well as the full recognition and use of English and French in Canadian society. One of the OLCDB’s key objectives is to improve access to health care services for OLMCs in the official language of their choice. To document this issue, Health Canada undertook a quantitative and qualitative data collection project to better understand the barriers that OLMCs may encounter in accessing health services in the official language of their choice, as well as enablers that facilitate this access. The results of this study will document the lived experience of OLMCs in accessing health care services in their official language of choice and will help identify key gaps and enablers.
Number of pages: 14

Perceptions from official language minority communities : Access to health services in the official language of choice 2020. Final report submitted to Health Canada. - Léger (2020)
This public opinion research report presents the results of a web survey and online focus group discussions conducted by Leger Marketing Inc. on behalf of Health Canada. The research was conducted with Canadians living in an official language minority situation. Health Canada, through the OLCDB, supports the implementation of activities to enhance the vitality and developments of OLMCs as well as the full recognition and use of English and French in Canadian society. One of the OLCDB’s key objectives is to improve access to health care services for OLMCs in the official language of their choice. To document this issue, Health Canada undertook a quantitative and qualitative data collection project to better understand the barriers that OLMCs may encounter in accessing health services in the official language of their choice, as well as enablers that facilitate this access. The results of this study will document the lived experience of OLMCs in accessing health care services in their official language of choice and will help identify key gaps and enablers.
Number of pages: 168

Challenges faced by bilingual stroke survivors in the healthcare system: Unique considerations - Sauvé-Schenk, Katrine; Dubouloz-Wilner, Claire-Jehanne; Egan, Mary; Kristjansson, Elizabeth (Linguistic Minorities and Society, 2020)
The experiences of multilingual patients communicating with unilingual healthcare providers have been largely unexplored. The aim of this study was to investigate the experiences of bilingual stroke patients within the Canadian healthcare context. A secondary analysis was completed with data from a multiple case study of the experiences of seven, low-income bilingual Francophone stroke survivors living in a predominately English area. Data included semi-structured interviews, chart reviews and language proficiency assessments. Results demonstrated that bilingual survivors experience unique challenges, including limited French health vocabulary, use of non-standard French, and generally low health literacy levels in both languages. Participants with aphasia often used English and French interchangeably, leading to the potential for miscommunication when providers were not bilingual. The study highlights the importance of having bilingual healthcare providers when bilingual stroke survivors have communication or cognitive limitations. Keywords: Stroke, language, bilingualism, healthcare, literacy

Improving the active offer of french language services - Savard, Jacinthe; Sauvé-Schenk, Katrine (Société Santé en français, 2020)